Verbalizing the Idea of Exclusiveness in BBC Travel Texts - Danylchenko, I. V. (Видавництво НДУ ім. Миколи Гоголя, 2019)
The article explores lexical, lexical-grammatical and grammatical means of verbalizing the idea of exclusiveness in BBC Travel texts. Defining exclusiveness as the state of being available to a limited group of people due to their privileged status or because of high cost of a product, the analysis of 60 BBC Travel articles suggests that the choice of linguistic means is delimited by the destination the authors describe: Europe, America, Asia, Africa or Middle East. The results of the analysis demonstrate that describing Europe the authors focus on its history, art and attractions, America is marked by its feel-good factors, Africa and Middle East are presented as exclusive due to their nature and authentic culture, and destinations in Asia are famous for their pristine nature and urbanization. The paper proves that the use of linguistic means is constrained by the topic and genre of discourse.
Keywords: media discourse; BBC Travel texts; verbalization; linguistic means